2022
DOI: 10.13057/biodiv/d230543
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Biological control agent for Spodoptera litura on vegetable plants

Abstract: Abstract. Damiri N, Pujiastuti Y, Mulawarman, Astuti DT, Afriani SR, Rahim SE. 2022. Short Communication: Biological control agent for Spodoptera litura on vegetable plants. Biodiversitas 23: 2609-2613. This study aimed to assess the population dynamics of Bacillus thuringiensis and its potency as a bio-agent against Spodoptera litura. The field study was conducted in Musi Banyuasin District, South Sumatra, Indonesia. Isolation and exploration of B. thuringiensis were carried out by taking the soil around the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Then, the absorption peaks are 2846.93 and 2956.87 cm -1 is the vibration of the C-H alkyl, then the C=C stretching of the alkene is seen at 1641.42 cm -1 [24]. The absorption peaks at 1344.38, 1398.39 and 1450.47 cm -1 are the C-H bending of alkanes, then the C-O stretching is seen at 1016.49 and 1109.07 cm -1 , then the peaks at 642.3 and 680.87 cm -1 are the C-H bending vibrational character of alkenes [25].…”
Section: Discussionmentioning
confidence: 98%
“…Then, the absorption peaks are 2846.93 and 2956.87 cm -1 is the vibration of the C-H alkyl, then the C=C stretching of the alkene is seen at 1641.42 cm -1 [24]. The absorption peaks at 1344.38, 1398.39 and 1450.47 cm -1 are the C-H bending of alkanes, then the C-O stretching is seen at 1016.49 and 1109.07 cm -1 , then the peaks at 642.3 and 680.87 cm -1 are the C-H bending vibrational character of alkenes [25].…”
Section: Discussionmentioning
confidence: 98%
“…Seaweed is quite abundant, thus during the past ten years, as demand for it has grown, seaweed agriculture has flourished. Consequently, a substantial quantity of seaweed waste is generated from diverse industrial procedures, including the food industry, which imposes strict quality standards on the seaweed [15]. Within a circular economy, these waste materials can be utilized as a third-generation biomass for various purposes such as pharmaceuticals, animal feed, agriculture, and biofuels.…”
Section: Seaweedsmentioning
confidence: 99%
“…The prospect of seaweed is supported by many bioactive compounds such as alkaloids, carotenoids, flavonoids, terpenes, tocopherols, peptides, polysaccharides and polyphenols [2]. Several studies reported that seaweed bioactive compound components can be antioxidants, antibacterial, anti-inflammatory, antidiabetic, antidiarrheal, antimicrobial, and antibacterial [3,4,5].…”
Section: Introductionmentioning
confidence: 99%